A personal thermophoretic sampler for airborne nanoparticles - Thayer, Daniel Lee, author; Marchese, Anthony, advisor; Volckens, John, advisor; Popat, Ketul, committee member; Prieto, Amy, committee member (Colorado State University. Libraries, 2010)
Engineered nanoparticles are materials with at least one dimension measuring less than 100 nm that are designed on the molecular scale to produce unique or enhanced properties that differ from the bulk material. However, the same properties that make engineered nanoparticles attractive to industry also may present potential health risks to the workers who manufacture them. Very little human exposure data exist for these particles, although they are known enter the body through a number of routes (e.g., respiration, dermal penetrations, and ingestion). Nanoparticles that enter the body can also translocate from one organ to another by virtue of their small size. A cost-effective personal sampler is necessary to evaluate levels of worker exposure to these materials to determine the relative levels of individual risk. Such a sampler must be capable of collecting nanoparticles with high efficiency for subsequent analysis of size, surface chemistry, morphology, and other properties. In addition, the sampler must be able to differentiate between incidental nanoparticles, which are nanoparticles that are naturally present in the environment, and engineered nanoparticles. As detailed in this thesis, a small thermal precipitator was designed to measure breathing-zone concentrations of airborne nanoparticles. The thermal precipitator samples aerosol by producing a 1000 °C cm ' temperature gradient between two aluminum plates (0.1 cm separation distance) using a resistive heater, a thermoelectric cooler, a temperature controller, and two thermistor sensors. The collection efficiency was evaluated for 15, 51, 100, and 240 nm particles at flow rates of 5 and 20 mL/min. Tests were also performed with a zero temperature gradient to determine losses in the device for measurement correction. The homogeneity of particle collection across the collection surface was evaluated using electron microscopy and imaging software. The results indicate that thermal precipitation is a feasible approach for personal monitoring of airborne nanoparticle concentrations in the workplace.
Covers not scanned.
Keywords: Nanoparticles -- Measurement